2019
DOI: 10.1111/ajco.13236
|View full text |Cite
|
Sign up to set email alerts
|

Higher frequency of the CTLA‐4+LAG‐3+ T‐cell subset in patients with newly diagnosed acute myeloid leukemia

Abstract: Aim Immune suppression based on alternative regulation of immune checkpoint proteins, for example, programmed cell death receptor‐1 (PD‐1) and cytotoxic T lymphocyte–associated molecule‐4 (CTLA‐4), which results in T‐cell exhaustion, contributes to cancer development and progression. In this study, we sought to characterize the distribution of CTLA‐4 and T‐cell lymphocyte activation gene‐3 (LAG‐3) expression on exhausted T cells in different T‐cell subsets from patients with acute myeloid leukemia (AML). Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…Although CTLA-4 plays a crucial role in prevention of autoimmunity, its activity can often contribute to evasion of anti-tumor immunity in cancer [ 70 ]. Upregulation of CTLA-4 was observed on T cell subsets of CML and AML patients [ 41 , 71 ]. Curiously, also leukemic cells from AML and CML patients can express CTLA-4 [ 72 ].…”
Section: Leukemia-derived Factors That Promote Immune Evasionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CTLA-4 plays a crucial role in prevention of autoimmunity, its activity can often contribute to evasion of anti-tumor immunity in cancer [ 70 ]. Upregulation of CTLA-4 was observed on T cell subsets of CML and AML patients [ 41 , 71 ]. Curiously, also leukemic cells from AML and CML patients can express CTLA-4 [ 72 ].…”
Section: Leukemia-derived Factors That Promote Immune Evasionmentioning
confidence: 99%
“…It is suggested that tumor cells express MHC-II to bind with LAG-3 and inhibit TCR signaling on effector T cells. As LAG-3 is overexpressed on T cells in CML and AML patients [ 71 , 81 ], it could be yet another way to evade immune response by leukemic cells [ 98 ].…”
Section: Leukemia-derived Factors That Promote Immune Evasionmentioning
confidence: 99%
“…In addition, cancer cells and AML cells are able to escape the host immune surveillance by inactivating cytotoxic T cells (CTLs) [18]. It has been demonstrated that T cell immune inhibitory receptors, also known as immune checkpoint receptors, such as program death-1 (PD-1), T cell immunoglobulin mucin 3 (Tim-3), cytotoxic T lymphocyte-associated molecule-4 (CTLA-4) and T cell lymphocyte activation gene-3 (LAG-3) have increased expression in T cells in patients with newly diagnosed and relapsed AML and murine AML models [19][20][21][22]. For example, leukemia progression resulted in increased regulatory T (Treg) cells and PD-1 ligand (PD-L1) + CD8+ T cells at tumor sites in a mouse AML model, and PD-L1 inhibitor treatment could restore the proliferation and cytotoxic function of T cells at tumor sites, reduce AML tumor burden, and increase overall survival [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…1a, b). We further analyzed the expression patterns of PD-1, PD-L1, and PD-L2 with other important ICs [7][8][9]. Subsequently, with Pearson's correlation analysis, we found that the expression of PD-1, PD-L1, or PD-L2 was positively associated with the expression of cytotoxic T-lymphocyte associated protein 4 (CTLA-4) (r = 0.259, P < 0.001; r = 0.435, P < 0.001; r = 0.269, P < 0.001, respectively) and lymphocyte activation gene-3 (LAG-3) (r = 0.275, P < 0.001; r = 0.276, P < 0.001; r = 0.160, P = 0.033, respectively) in the TCGA group (Fig.…”
mentioning
confidence: 99%